Characteristics Analysis of Public Buildings on the Tsunami Risk Area in Banda Aceh City - Soviana, Widya; Keumala Citra; Abidin, Zainal; Ramadhan, Misbahul (Department of Architecture, Faculty of Engineering, University of Muhammadiyah Aceh, 2024)
Public buildings are structures used to serve the activities of the community at large. These buildings become gathering places for many people at one time. As venues for community activities, the presence of public buildings in tsunami-prone areas can increase vulnerability for their users. Therefore, it is necessary to understand the characteristics of public buildings located in regions at risk of tsunamis. This study aims to determine the reliability of public buildings based on the distribution of building zones, building structures, building heights, and the orientation of building locations. The results show that there are 328 public building units spread across the study area, which have varying levels of tsunami risk from low, medium, to high. The percentage breakdown of building classifications includes government buildings (31.1%), educational facilities (40.5%), health services (6.1%), places of worship (17.1%), commercial buildings (2.1%), and other facilities (3.0%). In terms of zone distribution, public buildings are predominantly located in alert zones that have a high risk of tsunami disasters. The building structures are generally permanent, made of reinforced concrete, with the majority being two or three stories high. The buildings are distributed across sparse, medium, and dense locations. Buildings with good reliability characteristics, such as strong structures resistant to tsunami waves and medium to high building heights, can be considered as alternative vertical evacuation sites for tsunamis. In Banda Aceh, public buildings are mostly low-rise, while medium-rise buildings include office and health service buildings. To ensure safety and security, it is necessary to enhance the quality of public buildings in the future, especially in areas with high tsunami risk.